Effects of experimental nitrogen deposition on soil organic carbon storage in Southern California drylands. Issue 6 (27th December 2022) - Püspök, Johann F.; Zhao, Sharon; Calma, Anthony D.; Vourlitis, George L.; Allison, Steven D.; Aronson, Emma L.; Schimel, Joshua P.; Hanan, Erin J.; Homyak, Peter M.
Abstract: Atmospheric nitrogen (N) deposition is enriching soils with N across biomes. Soil N enrichment can increase plant productivity and affect microbial activity, thereby increasing soil organic carbon (SOC), but such responses vary across biomes. Drylands cover ~45% of Earth's land area and store ~33% of global SOC contained in the top 1 m of soil. Nitrogen fertilization could, therefore, disproportionately impact carbon (C) cycling, yet whether dryland SOC storage increases with N remains unclear. To understand how N enrichment may change SOC storage, we separated SOC into plant‐derived, particulate organic C (POC), and largely microbially derived, mineral‐associated organic C (MAOC) at four N deposition experimental sites in Southern California. Theory suggests that N enrichment increases the efficiency by which microbes build MAOC (C stabilization efficiency) if soil pH stays constant. But if soils acidify, a common response to N enrichment, then microbial biomass and enzymatic organic matter decay may decrease, increasing POC but not MAOC. We found that N enrichment had no effect on C fractions except for a decrease in MAOC at one site. Specifically, despite reported increases in plant biomass in three sites and decreases in microbial biomass and extracellular enzyme activities in two sites that acidified, POC did not increase. Furthermore, microbial C use and stabilization efficiency increased in a non‐acidified site, but without increasing MAOC. Instead, MAOC decreased by 16% at one of the sites that acidified, likely because it lost 47% of the exchangeable calcium (Ca) relative to controls. Indeed, MAOC was strongly and positively affected by Ca, which directly and, through its positive effect on microbial biomass, explained 58% of variation in MAOC. Long‐term effects of N fertilization on dryland SOC storage appear abiotic in nature, such that drylands where Ca‐stabilization of SOC is prevalent and soils acidify, are most at risk for significant C loss. Abstract : We sampled soils at four long‐term N‐fertilization sites to understand how atmospheric N deposition may affect SOC dynamics in Southern Californian drylands under acidifying versus non‐acidifying conditions. Non‐acidified soils were expected to build soil organic carbon (SOC) via increased plant growth and microbial C stabilization efficiency, but they did not accumulate C. In contrast, acidified soils lost Ca that destabilized mineral‐associated organic C in one of the sites, suggesting that long‐term effects of N fertilization on dryland C storage are of abiotic nature, such that drylands where Ca‐stabilization of SOC is prevalent may be most at risk for significant C losses.